Microencapsulação de óleo de andiroba em matriz de gelatina/goma arábica - Inácio, Mariana Regina (2025)
This study investigated andiroba oil microcapsules with different oil concentrations and the presence of transglutaminase, aiming to analyze their structural, thermal, and stability properties. The turbidity test indicated that pH 4 was ideal for the formation of microcapsules. Particles with andiroba oil were more uniform and larger than control samples, while non-crosslinked samples with transglutaminase showed irregular structures. Electron microscopy revealed that the microcapsules maintained their sphericity and encapsulation efficiency, with an increase in the average particle diameter as the oil concentration increased. The polydispersity index (PDI) indicated greater heterogeneity in the samples without transglutaminase, especially with higher oil concentrations. FTIR spectroscopic analyses confirmed the effective encapsulation of andiroba oil within the microcapsules, identifying its characteristic bands in the oil-containing samples. These bands were absent in the control samples, without oil, confirming the presence of andiroba oil in the matrix of the microcapsules. Thermal analysis showed that oil-containing samples underwent decomposition in four stages, suggesting higher thermal stability, while oil-free samples only underwent two stages. The presence of transglutaminase altered the thermal behavior, increasing the thermal resistance of the microcapsules due to the formation of cross-links between the proteins. This study demonstrated that both andiroba oil and transglutaminase influence the structure, homogeneity, and thermal stability of the microcapsules, highlighting the efficiency of the encapsulation process.